From endogenous growth to stationary state: The world economy in the mathematical formulation of the Ricardian system. Issue 3 (4th May 2017) - Salvadori, Neri; Signorino, Rodolfo
Abstract: We analyse international trade in a Pasinetti–Ricardo growth model in the world economy scenario in which several small trading countries coexist and international commodity prices are determined by the interplay of supply and demand amongst them. We demonstrate that all the trading countries eventually reach the stationary state, though this process is not monotonic and the dynamics of capital and population may actually push some countries towards the stationary state and others away from it. We also use our model to assess an argument which Malthus employed in the second edition of An Essay on the Principle of Population (1803) to support a policy of agricultural protectionism.